The influence of discipline, communication and competence on teacher performance through motivation as an intervening variable - Dinillah, George (Winter Journal: IMWI Student Research Journal, 2023)
The purpose of this research is done (1) to know the influence of discipline to motivation (2) to knowing the influence of communication to motivation (3) to knowing the influence of competence to motivation (4) to know the influence of discipline to teacher performance (5) to knowing the influence of communication to performance teacher (6) to knowing the influence of competence to performance teacher (7) to know the influence of motivation to performance teacher. Respondents in this study as many as people, 125 the respondents are teacher SMK 1 and 2 Taman pemalang district. As for testing on the research was conducted by test the validity of, and reliability testing structural equation modelling (SEM). The analysis proved that discipline significant impact on motivation with the value of CR equal 3,421, communication motivation with significant impact on the value of CR equal 3,056, significant impact on competence motivation with the value of CR equal 3,531, Discipline to depend on teacher performance showed the value of CR equal 2,335, as much as communication impact on teacher performance showed the value of CR equal 2,739, as much as competence to depend on teacher performance showed the value of CR equal 2,522 and motivation to depend on teacher performance showed the value of CR equal 3,168 as much as the result is greater than the value of CR table ( t table ) as much as 1,96